Effects of ACE inhibition and AT(1)-receptor antagonism on endothelial function and insulin sensitivity in essential hypertensive patients - VELİOĞLU ÖĞÜNÇ, AYLİZ; YAVUZ, DİLEK; HAKLAR, GONCAGÜL; KOÇ, MEHMET (SAGE PUBLICATIONS LTD, 2003)
Objective Disturbed endothelial function is closely associated with hyperinsulinaemia and insulin resistance in essential hypertension. The alms of this study were: 1) to evaluate whether the two alternative drugs, angiotensin-converting enzyme (ACE) inhibitors and Angiotensin 11 (Ang 11) antagonists, had comparable effects on glucose metabolism and endothelial function. 2) to determine whether they improve endothelial dysfunction through modulating insulin resistance and oxidative stress. Study design and methods Essential hypertensive patients were randomised into two groups: Twelve (nine patients in final analysis) patients were given enalapril (enalapril group), and twelve (nine patients in final analysis) were given losartan (losartan group). Twelve sex- and age-matched normotensive volunteers were included as controls. Before and after six months of treatment, endothelial function, insulin sensitivity and lipid peroxidation (TBARs) and NO metabolites (NOx) were evaluated. Results Endothelial function, measured as flow mediated dilatation (FMD), was improved in both of the treatment groups (p=0.0001). Calculated insulin sensitivity index also improved in the enalapril-treated group (p=0.05) but not in the losartan-treated group, compared with baseline levels. TBARS values decreased significantly in the enalapril group compared with baseline levels (p<0.001). FMD was positively correlated with insulin sensitivity index (r=0.32, p<0.05) and NOx levels (r=0.39, p=0.01) and negatively correlated with TBARS levels (r=-0.53, p=0.0002) in hypertensive patients. Conclusion Inhibition of the renin-angiotensin system, either with ACE inhibitors or AT(1)-receptor blockers improves endothelial dysfunction. ACE inhibition has prominent effects on improving insulin sensitivity and decreasing oxidative stress in essential hypertensive patients.
Keywords: hypertension; angiotensin-converting enzyme inhibitors; angiotensin II receptor antagonists; insulin resistance; vascular endothelium; oxidative stress; CONVERTING ENZYME-INHIBITORS; GLUCOSE-METABOLISM; NITRIC-OXIDE; ANGIOTENSIN; DYSFUNCTION; RESISTANCE; KININS; TOLERANCE; LOSARTAN